Insight, Cognitive Insight and Sociodemographic Features in Obsessive Compulsive Disorder Presenting with Reactive and Autogeneus Features - Katre ÇAMLI; M. Hakan TÜRKÇAPAR; A. Emre SARGIN (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: The aim of the present study was to test hypothesis that obsessive compulsive disorder (OCD) patients who have autogenous obsessions and reactive obsessions show different sociodemographic and clinical characteristics with different insight and cognitive insight levels. Method: Sixty-one patients diagnosed as OCD according to the Structured Clinical Interview for DSM-III-R (SCID-I) are recruited. 31 patients had reactive obsessions and 30 had autogenous obsessions. The sociodemographic characteristics of patients and the symptomatology were evaluated using psychiatric scales including SCID-I, Yale Brown Obsessive- Compulsive Scale (YBOCS), Yale Brown Obsessive-Compulsive Scale-Symptom Checklist (YBOCS-SC) and Beck Insight Scale. Results: The percentage of women in reactive obsessive group was higher and also this group had significantly less antipsychotic medication prescribed than the autogenous obsessive group. No significant difference was found for the other demographic variables. No significant difference was identified for the Beck Insight Self-Reflectiveness subscale but for the Self-Certainty subscale, reactive obsessives had higher scores. Although there was no significant difference for the composit index points, which is the subtraction of the two subscales, the p value was close to the limit. On the other hand YBOCS item- 11 scores which evaluates insight were higher in autogenous obsessives meaning low levels of insight. Conclusion: For the sociodemographic and clinical characteristics; there was no significant difference between the groups except gender distribution and antipsychotic medication. Our data about insight seems inconsistent but insight and cognitive insight can be different entities which show different levels of insight. Further investigation with different obsession types is needed.